2008
DOI: 10.1002/ajmg.a.32380
|View full text |Cite
|
Sign up to set email alerts
|

Humero‐radial synostosis, microcephaly, short corpus callosum, and abnormal genitalia in sibs

Abstract: We report on two male sib fetuses with humero-radial synostosis and thumb hypoplasia, microcephaly with simplified gyral pattern, short corpus callosum and ambiguous genitalia. The main clinical, anatomopathological and imaging findings are presented and compared with previous cases of humero-radial synostosis as a prominent manifestation and with the X-linked lissencephaly with ambiguous genitalia syndrome (X-LAG). To our knowledge, this combination of anomalies has never been described before, and we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Finally, a search of the London Dysmorphology Database (http://www.lmdatabases.com/) and Possum 5.2 (http://www.possum.net.au/) yielded another possible diagnosis: a syndrome reported by Guilherme et al, [2008] presenting mainly early death, microcephaly, ambiguous genitalia, and brain abnormalities. Nevertheless, in the latter hypothesis, humero‐radial synostosis and specific dysmorphic facial features are also observed allowing differentiation between the two entities.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, a search of the London Dysmorphology Database (http://www.lmdatabases.com/) and Possum 5.2 (http://www.possum.net.au/) yielded another possible diagnosis: a syndrome reported by Guilherme et al, [2008] presenting mainly early death, microcephaly, ambiguous genitalia, and brain abnormalities. Nevertheless, in the latter hypothesis, humero‐radial synostosis and specific dysmorphic facial features are also observed allowing differentiation between the two entities.…”
Section: Discussionmentioning
confidence: 69%
“…The syndromes, which can have HRS as part of their spectrum, include those described by Antley and Bixler (); Ives and Houston (); Pfeiffer and Braun‐Quentin (); and Keutel, Kindermann, and Möckel (). Guilherme et al () reported two siblings with HRS and other anomalies, which appear to be a separate entity from any of the above syndromes. Al‐Hassnan and Teebi () categorized HRS into five groups: craniosynostosis, symphalangism, limb reduction, with other skeletal defects, and secondary teratogens.…”
Section: Discussionmentioning
confidence: 98%
“…possum.net.au) yielded another possible diagnosis: a syndrome reported by Guilherme et al, [2008] presenting mainly early death, microcephaly, ambiguous genitalia, and brain abnormalities. Nevertheless, in the latter hypothesis, humero-radial synostosis and specific dysmorphic facial features are also observed allowing differentiation between the two entities.…”
Section: Discussionmentioning
confidence: 97%